2022
DOI: 10.3390/ijms232416170
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Tocotrienol Modulates Total-Body Irradiation-Induced Hematopoietic Injury in a Nonhuman Primate Model

Abstract: Radiation exposure causes acute damage to hematopoietic and immune cells. To date, there are no radioprotectors available to mitigate hematopoietic injury after radiation exposure. Gamma-tocotrienol (GT3) has demonstrated promising radioprotective efficacy in the mouse and nonhuman primate (NHP) models. We determined GT3-mediated hematopoietic recovery in total-body irradiated (TBI) NHPs. Sixteen rhesus macaques divided into two groups received either vehicle or GT3, 24 h prior to TBI. Four animals in each tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 85 publications
5
23
1
Order By: Relevance
“…On the contrary, in our TBI study, we observed that GT3 treatment increased CFU-GM from day 7 onwards (40). Taken together, these results further confirm the earlier published studies in mice and NHPs that show GT3 is highly competent in protecting the hematopoietic tissue by facilitating/inducing HPCs recovery (34,35,40), and thereby promoting radiation-induced reduction in BM hematopoiesis.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…On the contrary, in our TBI study, we observed that GT3 treatment increased CFU-GM from day 7 onwards (40). Taken together, these results further confirm the earlier published studies in mice and NHPs that show GT3 is highly competent in protecting the hematopoietic tissue by facilitating/inducing HPCs recovery (34,35,40), and thereby promoting radiation-induced reduction in BM hematopoiesis.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, in our current study, NHPs exposed to the same dose with PBI showed an accelerated recovery of CFU-GM in GT3-treated groups, noted as early as day 2, suggesting sparing of BM might have facilitated the recovery process. On the contrary, in our TBI study, we observed that GT3 treatment increased CFU-GM from day 7 onwards (40). Taken together, these results further confirm the earlier published studies in mice and NHPs that show GT3 is highly competent in protecting the hematopoietic tissue by facilitating/inducing HPCs recovery (34,35,40), and thereby promoting radiation-induced reduction in BM hematopoiesis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations